2007
DOI: 10.1097/01.iae.0000243032.33738.f7
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Age-Related Evaluation of Small Retinal Vessels by Scanning Laser Doppler Flowmetry

Abstract: In a group of subjects aged 21 years to 70 years, we detected an increase of Delta(VD-FD)/2 in the retinal temporal superior artery and vein with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Techniques such as scanning laser doppler flowmetry and scanning laser ophthalmoscopy 40,41 permit in vivo measurement of microcirculatory blood flow that is inaccessible in any other microcirculation. When coupled with imaging of the retinal vessels, estimates of retinal vessel wall thickness may be obtained, 40,41 providing a unique means of determining actual arteriolar and venular wall thickness, which is clearly of value in assessing the health of the microcirculation. Some studies have shown that these measures may track the microcirculatory response to therapy for hypertension and may identify increased cerebrovascular risk.…”
Section: Functional Measures Of the Retinal Microvasculature Complemementioning
confidence: 99%
“…Techniques such as scanning laser doppler flowmetry and scanning laser ophthalmoscopy 40,41 permit in vivo measurement of microcirculatory blood flow that is inaccessible in any other microcirculation. When coupled with imaging of the retinal vessels, estimates of retinal vessel wall thickness may be obtained, 40,41 providing a unique means of determining actual arteriolar and venular wall thickness, which is clearly of value in assessing the health of the microcirculation. Some studies have shown that these measures may track the microcirculatory response to therapy for hypertension and may identify increased cerebrovascular risk.…”
Section: Functional Measures Of the Retinal Microvasculature Complemementioning
confidence: 99%
“…OD was measured in reflection images and ID was measured in perfusion images. The algorithm on which the assessment of OD and ID is based was described previously in detail [17]. Analyses of diameters were performed offline with AFFPIA (SLDF version 3.7 by Welzenbach).…”
Section: Measurement Of Retinal Arteriolar Structurementioning
confidence: 99%
“…19 The mean retinal capillary blood flow was calculated in the area of interest and expressed as arbitrary units.…”
Section: Measurement Of Retinal Capillary Blood Flowmentioning
confidence: 99%
“…18 Thereby, vessel diameters are detected by AFFPIA in reflectivity images, as described previously. 19 The mean retinal capillary blood flow was calculated in the area of interest and expressed as arbitrary units.…”
Section: Measurement Of Retinal Capillary Blood Flowmentioning
confidence: 99%